Yield and crop cycle time of peaches cultivated in subtropical climates and subjected to different pruning times - Ferraz, Rafael Augusto [UNESP]; Leonel, Sarita [UNESP]; Segantini, Daniela Mota [UNESP]; Tecchio, Marco Antonio [UNESP]; Antunes, Luis Eduardo Corrêa (My University, 2015)
The cultivation of peaches in regions of subtropical and tropical climate is currently achieved through a set of practices such as using less demanding cultivars in cold conditions, applying plant growth regulators to break dormancy, and performing specific pruning, like production and renewal pruning. Research on the climate adaptation of cultivars is of great importance in establishing a crop in a given region. Therefore, the objective of this study was to evaluate the agronomic performance of three cultivars subjected to different production pruning times in Botucatu/SP, where 2-year old peach trees were evaluated, grown at a spacing of 6.0 x 4.0 meters. The experimental design was a split plot design with four blocks, using the cultivars Douradão, BRS Kampai and BRS Rubimel, and the subplots corresponded to pruning times in May, June, July and August. Ten plants were used per plot, with the four central plants considered useful and the remaining considered as margins. Pruning in June and July showed the best results in terms of percentage of fruit set and production. The cultivar BRS Rubimel showed the best percentage of fruit set when pruned in June (44.96%), and best fruit production when pruned in July (18.7 kg plant-1). Pruning in May anticipated the harvest of cultivar BRS Rubimel by 13 days whereas pruning carried out in July and August provided late harvests for cultivars Douradão and BRS Kampai.
Keywords: Agronomic performance; Peach; Production pruning; Prunus persica; Regional behavior